Exploring the role of the theory of planned behaviour, risk orientation, and participative leadership in SME managers’ engagement in CSR - Mohd Tan, Athirah; Ann, Ho Jo (Fundacao Escola de Comercio Alvares Penteado, 2023)
Purpose – The purpose of this study was to examine the antecedents that influence SME managers’ intentions to engage in corporate social responsibility (CSR) and whether these intentions translate into actual CSR engagement behaviour. Theoretical framework – This study used the Theory of Planned Behaviour to examine the influence of SME managers’ attitudes, subjective norms and perceived behavioural control on their intention to engage in CSR activities. Trait Theory and Expected Utility Theory were also used to explain the influence of risk orientation and participative leadership style on their attitudes towards CSR. Design/methodology/approach – Primary data were collected using questionnaires. The data, which consisted of 301 respondents, were analysed using PLS-SEM. Findings – Risk orientation and participative leadership style had a significant influence on the managers’ attitudes. Attitudes, subjective norms and perceived behavioural control were also found to have a significant effect on their intention to engage in CSR, which subsequently influenced their actual CSR behaviour. Practical & social implications of research – For policy makers, this study provides a reference for encouraging CSR engagement among SMEs. For managers and owners of SMEs, it identifies the antecedents that are important for a positive attitude towards CSR engagement. Originality/value – The findings enrich the literature on risk orientation and participative leadership, which are important antecedents of managers’ CSR attitudes. The findings also support the applicability of the Theory of Planned Behaviour in the area of CSR engagement in the context of SMEs.